Bovine amniotic membrane derived extracellular matrix scaffold for treatment of descemetocele in a Labrador Retriever dog - Krishnakanth, K.; Sooryadas, S.; Remya, V.; Kumar, N.S. Jinesh; Dinesh, P.T.; Rajani, C.V.; Hamza, P.; Anoop, S. (Indian Journal of Veterinary Surgery, 2026)
-